2019
DOI: 10.2298/vsp170225079s
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of peg-shaped and missing lateral incisors with maxillary impacted canines

Abstract: Background/Aim. Many authors find that impacted maxillary canines is associated with missing and peg-shaped lateral incisor. The aim of this study was to examine the prevalence of peg-shaped and missing lateral incisor in subjects with impacted maxillary canines, and compare the size of maxillary lateral incisor on the side with palatally impacted canines and on the opposite side of the jaw where there is no impaction. Methods. The study included 64 patients with 80 impacted maxillary canines (23 males and 41 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
2
3
0
Order By: Relevance
“…Bilateral impaction was present in 22.3% of the investigated impactions. These results are in consistency with recent literature findings where bilateral impactions were found in 20-25% of the cases 4,6,20 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Bilateral impaction was present in 22.3% of the investigated impactions. These results are in consistency with recent literature findings where bilateral impactions were found in 20-25% of the cases 4,6,20 .…”
Section: Discussionsupporting
confidence: 93%
“…Findings regarding gender indicate sexual dimorphism of CI, since females were twice more often affected compared to males, and these results agree with findings from the literature 5,6,20 . Sacerdoti and Baccetti 7 have found that females to males' prevalence of palatally displaced IC was in ratio 3:1.…”
Section: Discussionsupporting
confidence: 90%
“…According to a previous study done at the University of Baghdad, they suggest that buccal displacement of canines has the same influence as palatal displaced canines as both are often associated with different dental agenesis, impaction and anomalies (Rafeeq et al, 2020). In Kosovo, they found differences in width and length of lateral incisors in patients with palatal impacted canines in comparison to the control group where there is no impacted canine (Simić et al, 2019).…”
Section: Introductionmentioning
confidence: 96%
“…The etiology of canine impaction is multifactorial, encompassing both genetic and local factors 3,4 . The delay or complete cessation of tooth eruption may be due to a long and tortuous eruption pathway, trauma, improper position of the tooth germ, fibrous callus in mucoperiosteum, sclerotic changes in bone, mucosal thickening, existing impacted teeth, hyperdontia, odontoma, cysts, tumors, etc.…”
Section: Introductionmentioning
confidence: 99%